VISUALISASI PEREMPUAN KORBAN KEKERASAN DALAM FOTOGRAFI EKSPRESI - I Putu Angga Mertha Pratama; I Made Bayu Pramana; Cokorda Istri Puspawati Nindhia (Retina Jurnal Fotografi, 2022)
Violence against women is still a global phenomenon that continues to occur. The forms of violence that occur include physical, sexual and verbal violence that have a negative impact on the victims. Seeing this phenomenon, the Janahita Mandala Ubud Foundation formed a program called Wadhu Wakya which is an effort to raise women's issues and create a gender vortex that women have a significant role. large. From these problems, it inspires the author to visualize violence against women into expression photography which aims as a means to increase public knowledge about the issue of violence against women and increase awareness of behavior not to take such actions. The study of sources used in this creation are several books, journals, and articles related to violence against women and the visualization of expression photography. The implementation method used is non-participant observation and interview methods. The photos that have been made are expected to be able to help inform about various forms of violence against women and the impacts caused and experienced by victims of violence, increase sympathy and actively participate in campaigning for the anti-violence movement based on gender. Keywords: Visualization, Violence, Women, Expression Photography.